The analysis of ethnocultural problems in F.Gyulen's works (Journal of Philosophy Culture and Political Science, 2019)
The article deals with ethnic and cultural issues in the works F.Gyulen. By studying the works of F. Gulen on ethno-cultural issues gives the deﬁ nitions for «People's Land», «mother tongue», «popular culture».